Efficient Chemoenzymatic Synthesis of N‐Glycans with a β1, 4‐Galactosylated Bisecting GlcNAc Motif. (19th August 2020) - Weiss, Michael; Ott, Dimitri; Karagiannis, Theodoros; Weishaupt, Markus; Niemietz, Mathäus; Eller, Steffen; Lott, Marie; Martínez‐Orts, Mónica; Canales, Ángeles; Razi, Nahid; Paulson, James C.; Unverzagt, Carlo
Abstract: In human serum immunoglobulin G (IgG), a rare modification of biantennary complex N‐glycans lead to a β1, 4‐galactosylated bisecting GlcNAc branch. We found that the bisecting GlcNAc on a biantennary core‐fucosylated N‐glycan was enzymatically galactosylated under stringent reaction conditions. Further optimizations led to an efficient enzymatic approach to this particular modification for biantennary substrates. Notably, tri‐ and tetra‐antennary complex N‐glycans were not converted by bovine galactosyltransferase. An N‐glycan with a galactosylated bisecting GlcNAc was linked to a lanthanide binding tag. The pseudo‐contact shifts (PCS) obtained from the corresponding Dy‐complex were used to calculate the conformational preferences of the rare N‐glycan. Besides two extended conformations only a single folded conformation was found. Abstract : From analytical oddity to conformational study . A rare N‐glycan with a galactosylated bisecting GlcNAc present in human serum immunoglobulin (IgG1) was obtained by chemoenzymatic synthesis from A and derivatized with a lanthanide tag (B ). Paramagnetic NMR studies revealed a conformational behavior deviating from that of the non‐bisected biantennary N‐glycan.